The influence of the chosen method of anesthesia on the severity of postoperative cognitive dysfunction in patients with ophthalmic surgery - Dorofeeva , G.S. (Medicni Perspektivi, 2021)
Reduction of cognitive functions in the postoperative period is gaining importance in the context of the insurance medicine introduction. Operational stress and anaesthetization are factors which increase the risk of deepening and developing postoperative cognitive dysfunction. The function of short-term memory, attention function, and the speed of psychomotor cognitive reactions are the most vulnerable to the action of general anesthetics. The influence of various methods of anesthesia on cognitive functions in ophthalmic surgery patients after end-to-end keratoplasty has been studied in this research work. Dexmedetomidine was used (the selective agonist of α-adrenoreceptors) as one of the components of multimodal anaesthetization. The sedative effect of this drug is explained by inhibition of neural activity in the blue spot of the brain stem. Dexmedetomidine is known to be used for sedation of patients. It allowed possibility to reduce the amount of fentanyl which was necessary for intra-and post-operative anaesthetization. Our research was conducted on the basis of ME "DRCOH". 78 patients at the age of 18 to 60 years were examined after end-to-end keratoplasty. Non-inclusion criteria: presence of concomitant pathology, neurological diseases, use of psychotropic substances and alcohol 6 months before the study. The study was conducted using neuropsychological testing: the Mini Mental State Examination (MMSE),the Frontal Assessment Battery (FAB), and Luria’s test. Testing was performed before the operation, in 6, 24 hours, 7 and 21 days. Patients were randomized into two groups. The first group – group k (n1=45) included patients who were provided with anaesthetic management according to the following scheme:premedication — ondansetron 4 mg, dexamethasone 4 mg, ketorolac 30 mg intravenously, sibazone 10 mg, fentanyl 0.1 mg intramuscularly 40 minutes before intervention. Induction of propofol – 2-2.5 mg/kg fractionally to achieve clinical symptoms of anaesthetization, fentanyl – 0.005% 0.1 mg tracheal intubation after relaxation on the background of atracuriumbenzylate – 0.3-0.6 mg/kg. Maintaining of anaesthetization: oxygen-sevoflurane mixture FiO250-55%, sevoflurane 1,4-1,8 vol.% on exhalation (1-1. 5 WT.) with the flow of no more than 1 l/min. BIS indicators were kept at the level of 30-40, during the surgery, the bolus injection of 0.1 mg of fentanyl was used in the event of hemodynamic reactions. Anaesthetic support was performed using the infusion of dexmedetomidin for 40 minutes, ondansetron 4 mg, dexamethasone 4 mg, ketorolac 30 mg intravenously in the second group d (n2=33). Induction, relaxation and maintenance of anaesthetization were performed as in the previous group. Intra-operative monitoring of patients in both groups included: non-invasive measurement of blood pressure (BP), heart rate (HR), pulse oximetry, determination of blood gases (oxygen, carbon dioxide and inhaled anesthetic on inhalation and exhalation). Control of the depth of anaesthetization was performed on the basis of BIS and ANI - monitoring. The use of dexmedetomidinu as the component of a multi-modal method of anaesthetizational al lowed obtaining less pronounced POCD, due to the reduction in the number of used drugs. Further use of the combination of highly selective agonists of α2-adrenoreceptors with regional anaesthetization in ophthalmic surgery is the promising method.